CTNNB1 Signaling in Sertoli Cells Downregulates Spermatogonial Stem Cell Activity via WNT4 - Boyer, Alexandre; Yeh, Jonathan R.; Zhang, Xiangfan; Paquet, Marilène; Gaudin, Aurore; Nagano, Makoto C.; Boerboom, Derek (PLOS ONE, 2012)
Constitutive activation of the WNT signaling effector CTNNB1 (β-catenin) in the Sertoli cells of the Ctnnb1tm1Mmt/+;Amhr2tm3(cre)Bhr/+ mouse model results in progressive germ cell loss and sterility. In this study, we sought to determine if this phenotype could be due to a loss of spermatogonial stem cell (SSC) activity. Reciprocal SSC transplants between Ctnnb1tm1Mmt/+;Amhr2tm3(cre)Bhr/+ and wild-type mice showed that SSC activity is lost in Ctnnb1tm1Mmt/+;Amhr2tm3(cre)Bhr/+ testes over time, whereas the mutant testes could not support colonization by wild-type SSCs. Microarray analyses performed on cultured Sertoli cells showed that CTNNB1 induces the expression of genes associated with the female sex determination pathway, which was also found to occur in Ctnnb1tm1Mmt/+;Amhr2tm3(cre)Bhr/+ testes. One CTNNB1 target gene encoded the secreted signaling molecule WNT4. We therefore tested the effects of WNT4 on SSC-enriched germ cell cultures, and found that WNT4 induced cell death and reduced SSC activity without affecting cell cycle. Conversely, conditional inactivation of Wnt4 in the Ctnnb1tm1Mmt/+;Amhr2tm3(cre)Bhr/+ model rescued spermatogenesis and male fertility, indicating that WNT4 is the major effector downstream of CTNNB1 responsible for germ cell loss. Furthermore, WNT4 was found to signal via the CTNNB1 pathway in Sertoli cells, suggesting a self-reinforcing positive feedback loop. Collectively, these data indicate for the first time that ectopic activation of a signaling cascade in the stem cell niche depletes SSC activity through a paracrine factor. These findings may provide insight into the pathogenesis of male infertility, as well as embryonic gonadal development.